Association of Mannose-Binding Lectin Deficiency with Acute Invasive Aspergillosis in Immunocompromised Patients - Lambourne, Jonathan; Agranoff, Dan; Herbrecht, Raoul; Troke, Peter F.; Buchbinder, Aby; Willis, Fenella; Letscher-Bru, Valérie; Agrawal, Samir; Doffman, Sarah; Johnson, Elizabeth; White, P. Lewis; Barnes, Rosemary A.; et al. (Clinical infectious diseases, 2009)
Background. Invasive aspergillosis is a devastating infection with attributable mortality of 40% despite antifungal therapy. In animal models of aspergillosis, deficiency of mannose-binding lectin (MBL), a pattern recognition receptor that activates complement, is a susceptibility factor. MBL deficiency occurs in 20%-30% of the population. We hypothesized that MBL deficiency may be a susceptibility factor for invasive aspergillosis in humans. Methods. Serum MBL concentrations were measured by enzyme-linked immunosorbent assay in 65 patients with proven or probable acute invasive aspergillosis and 78 febrile immunocompromised control subjects. MBL concentrations and the frequency of MBL deficiency were compared. Results. The median serum MBL level was significantly lower in patients with aspergillosis than in control subjects (281 ng/mL vs 835 ng/mL; P=.007). MBL deficiency (MBL concentration, <500 ng/mL) was significantly more common in patients with aspergillosis than control subjects (62% vs 32%; P<.001). Frequency of MBL deficiency was similar among patients with aspergillosis irrespective of response to antifungal therapy (P=.10). Conclusions. This study is the first, to our knowledge, to show an association between MBL deficiency and acute invasive aspergillosis in humans. Further study is required to investigate the causal nature of this association and to define whether diagnosis of MBL deficiency may identify immunocompromised patients at increased risk of invasive aspergillosis.